The mediation role of psychological capital between family relationship and antenatal depressive symptoms among women with advanced maternal age: a cross sectional study - Kai Zeng; Yang Li; Rumei Yang (BMC, 2022)
Abstract Background Due to changes in family policy in China, pregnancy at advanced age (30 years old or above) is prevalent. Advanced maternal age is known to be related to a variety of negative health outcomes, including antenatal depression. Family relationship quality might be an important factor for antenatal depressive symptoms among Chinese women with advanced maternal age. However, the underlying mechanisms in which family relationship quality can affect antenatal depressive symptoms among this population and how positive psychological capital (PsyCap) intervenes in this impact are not clear. Objectives To describe the prevalence and demographic characteristics of antenatal depressive symptoms among Chinese pregnant women with advanced maternal age, and to explore the mediation effect of PsyCap in the associations between family relationship quality and antenatal depressive symptoms. Methods We conducted a cross-sectional survey at a tertiary hospital in China. A total of 192 women with maternal age of 30 years or older completed the questionnaires. Data on antenatal depressive symptoms, PsyCap, family relationship quality and demographic characteristics were collected. The multiple mediation models in SPSS's PROCESS macro were used to test whether PsyCap mediated the relationship between family relationship quality and antenatal depressive symptoms. Results Approximately 28.6% of participants had antenatal depressive symptoms and 6.8% reported poor family relationship quality. Participants with higher education (p = .02) and better family relationship quality (p = .00) were less likely to have antenatal depressive symptoms. PsyCap collectively (β = 1.14, p < .05), or more specifically resilience (β = 0.61, p < .05) significantly mediated the relationship between poor family relationship quality and antenatal depressive symptoms. Discussion The relationship between family relationship quality and antenatal depressive symptoms can be mediated by PsyCap collectively or via resilience specifically. It is important to screen antenatal depressive symptoms among pregnant women with advanced age, especially those who have poor family relationship quality. Counseling and psychotherapy initiatives for resilience-enhancing training for pregnant women at advanced age may provide a promising target to break the link between poor family relationship quality and antenatal depressive symptoms.